Effect of yoga on health-related quality of life in central nervous system disorders: A systematic review. (November 2021) - Lenoir dit Caron, Rita; Coquart, Jeremy; Gilliaux, Maxime
Objective: Investigate the effect of yoga on health-related quality of life (HRQoL) in patients with central nervous system disorders. Methods: A systematic search was conducted on the PubMed-NCBI, EBSCO Host, Cochrane Library, Scopus and ScienceDirect databases until 05 April 2021. Only randomized control trials published in English or French were included and had to compare yoga to another intervention group or a control group. They also had to clearly measure HRQoL. Methodological quality was assessed with the revised Cochrane risk-of-bias tool for randomized trials and the quality of evidence was evaluated using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) criteria. Results: Sixteen studies were found, including six for multiple sclerosis, five for Parkinson's disease, two for stroke, one for dementia, one for epilepsy and one for brain tumour. Only 12 studies performed between-group statistics and 8 found a significant difference between groups after treatment. When yoga was compared to no intervention, the results were generally in favour of the yoga group, but when yoga was compared to another intervention programme, there was generally no significant difference between groups. There were many different HRQoL questionnaires, even within the same disease, which reduces the comparability of studies. Conclusions: With low to moderate quality of the evidence, yoga seems effective to improve HRQoL in people with Parkinson's disease. For multiple sclerosis, stroke, dementia, epilepsy and brain tumour, the quality of the evidence is still insufficient to conclude of the effectiveness of yoga.